Ageing with Health and Dignity - Peter P. Yuen (ACHSM, 2020)
I am grateful to be given the opportunity to write this Editorial. As mentioned by Dr. Briggs's introduction ("In this Issue"), the articles in this Special Issue were selected from papers presented to the CPCE Health Conference 2020 in Hong Kong. The 2020 Conference is the fifth consecutive annual conference organized by the College of Professional and Continuing Education (CPCE) of The Hong Kong Polytechnic University, supported by many partner institutions, including the Australasian College of Health Services Management and the APJHM.....